"Chicagónak indult, Barcs lett belőle..." Barcs gazdasági fejlődése a dualizmus korszakában: „CHICAGO STARTED BARCS CAME OF IT…” DEVELOPEMENT OF THE ECONOMY OF BARCS IN THE ERA OF DUALISM - Szabó, Máté (Közép-Európai Közlemények, 2021)
At the very beginning of my essay I point out that what kind of natural and economical conditions Barcs have had in the 19th century. This is important becouse I had to place Barcs into this medium, which in the beginning of the 19th was a simple manorial village situated in the flood plain of the Drava. The Drava river had a great impact on the improvement of the village. This little manorial village by the end of the century became one of the determinative villages in the region of southern Transdanubia. I show why was the location of the village so importan at that time. As a vehicular interchange and with its warehouse capacity by the beginning of the 20th century it was significant too. There were five railway lines that are met in Barcs in the begining of the 20th century. So it was a significant vehicular intersection at that time. Furthermore after Kaposvár it was the second biggest idustrial centre of the county. By this time it was famous about its wood and mill industries across Europe. Moreover it had a regional centre role at different types of food industries. I introduce to what kind of economical processies and infrastructural investments helped the large economical developement of the village. At the end of my essay I want to show the series of events which crash this tremendous economical and social change in barcs after the I. World War. A dolgozatom elején ismertetem Somogy megye természeti és gazdasági viszonyait a 19. századra vonatkozóan. Ez azért fontos, hogy ebben a közegben elhelyezhessem Barcsot, amely a 19. század elején még egy, a Dráva árterületén fekvő egyszerű uradalmi falu volt. A Dráva folyónak nagy hatása volt a település fejlődésére. Ez a kis falu a század végére a dél-dunántúli régió egyik meghatározó településévé vált. Közlekedési csomópontként és raktározási kapacitásaival a 20. század elejére országos viszonylatban is kiemelkedővé, továbbá Somogy megye, Kaposvár utáni másodig legnagyobb ipari központjává vált. Európa szerte híres volt a korszerű faiparáról és malomiparáról. Továbbá régiós központi szerepe volt különböző fajta élelmiszeriparokban. Ismertetem, hogy milyen gazdasági folyamatok és infrastruktúrális beruházások segítették a település nagymértékű gazdasági fejlődését. A dolgozatom végén megmutatom az események sorozatát, amelyek megtörték ezt a hatalmas gazdasági és társadalmi változást Barcson az I. Világháború után.